2015
DOI: 10.1371/journal.pone.0141547
|View full text |Cite
|
Sign up to set email alerts
|

Renal Interstitial Arteriosclerotic Lesions in Lupus Nephritis Patients: A Cohort Study from China

Abstract: ObjectiveThe aim of this study was to evaluate renal arteriosclerotic lesions in patients with lupus nephritis and investigate their associations with clinical and pathological characteristics, especially cardio-vascular features.DesignA retrospective cohort study.ParticipantsSeventy-nine patients with renal biopsy-proven lupus nephritis, diagnosed between January 2000 and June 2008 from Peking University First Hospital.ResultsIn clinico-pathological data, patients with arteriosclerosis had higher ratio of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…28 But this was not statistically significant in this study probably because of the small number of cases. Vascular changes such as arteriolar sclerosis and arterial sclerosis have also been suggested to be a harbinger of poor prognosis by Huang J et al 29 These too have not been found to be significant in our series.…”
Section: Discussioncontrasting
confidence: 46%
“…28 But this was not statistically significant in this study probably because of the small number of cases. Vascular changes such as arteriolar sclerosis and arterial sclerosis have also been suggested to be a harbinger of poor prognosis by Huang J et al 29 These too have not been found to be significant in our series.…”
Section: Discussioncontrasting
confidence: 46%
“…Several factors may predispose patients with SLE to respiratory failure, including pulmonary lesions, such as those in the airway [ 12 ], vessels [ 19 ], interstitium [ 11 ], and pleura [ 41 ]; and extrapulmonary lesions such as those in the brain [ 11 ], kidneys [ 10 ], and heart [ 11 ]. In patients with SLE, the functions of these organs progressively deteriorate [ 46 ], which is associated with incident comorbidities [ 18 , 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent population-based study in Taiwan reported that the average incidence of SLE cases between 2003 and 2008 was 4.87 per 100 000 person-years [ 5 ]. SLE is an autoimmune disease that affects multiple organ systems [ 6 ] such as the heart, joints, skin, lungs [ 7 , 8 ], chest wall, pleura, vessels [ 9 ], liver, kidneys [ 10 ], and nervous system [ 11 ]. SLE is associated with an increased risk of incident lung diseases (e.g., obstructive airway disease [ 7 , 12 ], pneumonia [ 8 ], and pulmonary embolism [ 13 ]), pleurisy and pleural effusion [ 14 ], and incident atherosclerosis-related diseases (e.g., hypertension [ 15 ], diabetes [ 16 ], stroke [ 15 , 17 ], and end-stage renal diseases; ESRD [ 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent data have shown that in 79 patients with biopsy-proven LN, 50 had arteriosclerosis lesions on renal biopsy. Patients with arteriosclerosis presented with more severe echocardiographic indices, including a larger left atrial diameter, left ventricular end-diastolic diameter, and interventricular septum thickness as compared with those of patients without any vascular changes [16]. As patients with SLE experience greater risks from cardiovascular events compared to healthy matched controls, non-immunosuppressive therapies and modification of cardiovascular risk factors, including smoking cessation, glycemic control, and medications, such as renin-angiotensin system inhibitor and statin, should also be recommended for these patients [70,71].…”
Section: Therapeutic Strategies For Renal Microvascular Lesions In Lnmentioning
confidence: 93%
“…More than one-third of the lupus patients with renal atherosclerosis were combined with ICD [16], suggesting its involvement in this change formation. A deficiency of complement factors in both the classic and lectin pathway, including complement component 1q (C1q), mannose-binding lection (MBL), and complement component 3 (C3), in a low-density lipoprotein receptor-deficient (LdlrÀ/À) murine model of lupus has been shown to result in larger atherosclerotic lesions.…”
Section: Arteriosclerosis (As)mentioning
confidence: 99%